The divine pathos in Jewish philosophy - Sevilla Godínez, Héctor (ARFIL y UNL, 2022)
In this article it is intended to clarify the meaning of the pathos of the divine as an attribute of emotionality in God. Some essential aspects of the Jewish tradition are pointed out, referring to the links and thematic controversies between Heschel, Maimonides and Spinoza regarding the attributes of God and his relationship with men. It alludes to the criticism that Spinoza directed to the Jewish tradition and the consequences of that attitude for the Dutch thinker, including the rejection of other students of Judaism. Finally, some of the recent criticisms of the anthropomorphic conception of the divine and the implications of assuming that God has emotions are explained.